Ophthalmoniphetodes - tertiäre Relikte im Schnee (Coleoptera, Staphylinidae, Omaliinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2006)
The genus Ophthalmoniphetodes Zerche, 1990 is revised and redescribed. Its phylogenetic relationships as well as the hierarchical subordination within the genus are re-examined and analysed. All 56 species are oligostenothermic inhabitants of permanent cold crevices and cavities under and within the snow layer and snow fields. In their ecological niche they are practically without competition. The range of the genus includes mountain ranges and massifs in Bulgaria, Greece and Serbia. All species are local endemics. They survived the Pleistocene principally in their recent ranges. As Tertiary relicts the Ophthalmoniphetodes species are of outstanding biogeographic importance.